Oral complications during the two waves of COVID-19 pandemic in China: a prospective cross-section analysis of 510 cases using questionnaire - Bojing Qu; Honglin Liu; Wanli Zhu; Minghui Wei; Wen Yin; Qing Liu; Zhenlai Zhu (BMC, 2024)
Abstract Background Oral complications such as parageusia, xerostomia, and oral ulcers are frequently observed in patients with COVID-19. The aim of this study was to understand the oral complications and their influencing factors during the two waves of the COVID-19 pandemic in China between December 2022 and May 2023. Methods A total of 347 patients during the COVID-19 pandemic from December 2022 and January 2023 and 163 patients during the second COVID-19 pandemic were recruited through the Disease Prevention and Control Reporting System. Data on oral complications were collected via researcher-made questionnaires. Results During both pandemic periods, more than 50% of the subjects developed oral complications. Specifically, the incidence of parageusia, pathological tongue coating, and xerostomia all exceeded 20%, while the incidence of oral ulcers surpassed 7%. Patients with allotriosmia and xerostomia had a significantly higher likelihood of developing other oral complications. Hospitalized patients requiring supplemental oxygen had a significantly higher incidence of oral complications. Conclusions The results of our study underline that oral complications during the COVID-19 pandemic are prevalent, and their incidence has not decreased during the subsequent pandemic. In the context of the ongoing global spread of COVID-19, this study lays the foundation for physicians in recognizing and managing oral complications, which will improve the oral health of communities globally.